Theoretical activity prediction, structure-based design, molecular docking and pharmacokinetic studies of some maleimides against Leishmania donovani for the treatment of leishmaniasis - Ugbe, Fabian Audu (2023)
Leishmaniasis is a neglected tropical disease caused by a group of protozoan of the genus Leishmania and transmitted to humans majorly through the bite of the female sand fly. It is prevalent in the tropical regions of the world especially in Africa and estimated to affect a population of about 12 million people annually. This theoretical study was therefore conducted in support of the search for more effective drug candidates for the treatment of leishmaniasis. This study focuses on the in silico activity prediction of twenty-eight (28) maleimides, structure-based design, molecular docking study and pharmacokinetics analysis of the newly designed maleimides. All the studied compounds were drawn using ChemDraw Ultra and optimized by the density functional theory (DFT) approach using B3LYP with 6-31G⁄ basis set.